Astragalus polysaccharide restores insulin secretion impaired by lipopolysaccharides through the protein kinase B /mammalian target of rapamycin/glucose transporter 2 pathway - Xiaodan Ren; Ying Dai; Mengya Shan; Jing Zheng; Zhongyi Zhang; Tao Shen (BMC, 2023)
Abstract Background Lipopolysaccharide (LPS)-induced dysfunction of pancreatic β-cells leads to impaired insulin (INS) secretion. Astragalus polysaccharide (APS) is a bioactive heteropolysaccharide extracted from Astragalus membranaceus and is a popular Chinese herbal medicine. This study aimed to elucidate the mechanisms by which APS affects INS secretion from β-cells under LPS stress. Methods Rat insulinoma (INS-1) cells were treated with LPS at a low, medium, or high concentration of APS. Glucose-stimulated insulin secretion (GSIS) was evaluated using an enzyme-linked immunosorbent assay (ELISA). Transcriptome sequencing was used to assess genome-wide gene expression. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis was used to determine the signaling pathways affected by APS. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was performed to evaluate the gene expression of glucose transporter 2 (GLUT2), glucokinase (GCK), pancreatic duodenal homeobox-1 (PDX-1), and INS. Western blot analysis was used to detect the protein expression of phosphorylated protein kinase B (p-Akt), total Akt (t-Akt), phosphorylated mammalian target of rapamycin (p-mTOR), total mTOR (t-mTOR), and GLUT2. Results LPS decreased GLUT2, GCK, PDX-1, and INS expression and reduced GSIS. These LPS-induced decreases in gene expression and GSIS were restored by APS treatment. In addition, transcriptome sequencing in combination with KEGG enrichment analysis revealed changes in the INS signaling pathway following APS treatment. LPS decreased p-Akt and p-mTOR expression, which was restored by APS treatment. The restorative effects of APS on GSIS as well as on the expression of GLUT2, GCK, PDX-1, and INS were abolished by treatment with the Akt inhibitor MK2206 or the mTOR inhibitor rapamycin (RPM). Conclusions APS restored GSIS in LPS-stimulated pancreatic β-cells by activating the Akt/mTOR/GLUT2 signaling pathway.